1999
DOI: 10.1093/emboj/18.20.5592
|View full text |Cite
|
Sign up to set email alerts
|

The Aspergillus nidulans sfaD gene encodes a G protein beta subunit that is required for normal growth and repression of sporulation

Abstract: flbA encodes an Aspergillus nidulans RGS (regulator of G protein signaling) domain protein that antagonizes FadA (G i α-subunit of heterotrimeric G protein)-mediated growth signaling to allow asexual development. We previously defined and characterized five suppressors of flbA (sfa) loss-of-function mutations and showed that one suppressor (sfaB) resulted from a novel dominant-negative allele of fadA. In this report we show that a second suppressor gene (sfaD) is predicted to encode the β subunit of a heterotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
163
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 141 publications
(172 citation statements)
references
References 34 publications
8
163
1
Order By: Relevance
“…We found that, while the DsfaD and DgpgADsfaD mutants produced conidiophores within 22 hr of liquid submerged culture, neither the DgpgA mutant nor WT produced conidiophores (Figure 4). Taken together, these results suggest that SfaD (Gb) plays a crucial role in negative regulation of conidiation under submerged culture conditions (Rosén et al 1999;Han et al 2004b) and GpgA may not be involved in this controlling process (see discussion).…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…We found that, while the DsfaD and DgpgADsfaD mutants produced conidiophores within 22 hr of liquid submerged culture, neither the DgpgA mutant nor WT produced conidiophores (Figure 4). Taken together, these results suggest that SfaD (Gb) plays a crucial role in negative regulation of conidiation under submerged culture conditions (Rosén et al 1999;Han et al 2004b) and GpgA may not be involved in this controlling process (see discussion).…”
Section: Resultsmentioning
confidence: 82%
“…Deletion of gpgA causes severe impairment in fruiting body formation: Our previous study showed that mutational inactivation of SfaD had profound negative effects on sexual fruiting body (cleistothecium) formation (Rosén et al 1999). To examine the possible role of GpgA in sexual development, we determined levels of Hülle cells and cleistothecia production in the DgpgA mutant.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations